COMPUTERIZED PAYMENT SYSTEM IN CIGARETTE AGENTS BETAWI JAYA - Syarifudin Syarifudin; Yuce Yuliani, SKom, MM. (Jurnal Sistem Informasi, 2002)
Payment system is less efficient to manually goods in terms of data processing sales transactions. But if it uses a computerized payment system will simplify the process transaction data processing, checking the amount of goods available and making reports to the head shop. Role of the computer to function as a data storage medium, in the process of data processing sales transactions, to prevent the loss of an invoice (bill) on sales that may be caused by slips or scattered. Tools to perform data processing goods in a sale of goods payment system. and as a means to process input into output in the form of an invoice (bill) from sales of goods and daily sales reports.